A186 OLDER AGE IS ASSOCIATED WITH INCREASED EXTRAINTESTINAL MANIFESTATIONS IN INFLAMMATORY BOWEL DISEASE. (4th March 2021) - Chattha, Z; Chattha, R; Reza, S; Moradshahi, M; Fadida, M; Naddaf Dezfooli, N; Piracha, Y; Mann, R; Singh, G; Samji, K; Narula, N
Abstract: Background: The relationship between older age and extraintestinal manifestations (EIMs) in patients with inflammatory bowel disease (IBD) remains unknown. Aims: This study aims to determine whether older age is associated with increased risk of EIMs in IBD patients. Methods: This was a retrospective study of IBD patients seen at the McMaster University Medical Centre, in Hamilton, ON, Canada from 2012–2020. Patients were identified to have the primary outcome of interest if their gastroenterologist documented the presence of any EIM either during the baseline assessment or during the period of follow up. The independent variable, age at start of follow-up, was dichotomized into two categories age >=40 vs. <40.Prior knowledge in combination with forward selection was used to develop a logistic regression model. The variables utilized for the forward selection model included gender, disease duration, and current biologic use. Results: A total of 995 IBD patients (625 with CD) were considered for the regression analysis, all for whom the EIM status was recorded. Out of the 995 patients, 270 patients reported at least one EIM – 99 with arthritis/arthralgia, 79 with dermatologic manifestations, 16 with ophthalmic manifestations, 30 with liver manifestations, and 116 with other EIMs. A univariate regression analysis foundincreased odds of EIMs in older patientsas compared to younger patients (odds ratio (OR) 1.41 (95% CI, 1.05 – 1.89)). In the multivariate regression analysis, current biologic use was found to have a significant relationship with odds of having EIMs (OR 1.49; 95% CI, 1.06 – 2.09). After adjustment for biologic use, patients aged 40 or over had 1.46 times higher odds of having EIMs (95% CI 1.03 – 2.05). A sub-analysis of individual EIM categoriesdid not show a significant association with older age. Conclusions: Older age is associated with increased risk of EIMs in IBD patients. Patients with EIMs were also more likely to be treated with biological therapies. Clinicians should inquire about the presence of EIMs in older IBD patients. Funding Agencies: None